PROJECT QUALITY: AN EMPIRICAL ANALYSIS OF PROJECT COMMUNICATION STRUCTURE AND CLIMATE AMONG CONSTRUCTION FIRMS IN NORTH CENTRAL NIGERIATY OF CONSTRUCTION FIRMS IN NORTH CENTRAL, NIGERIA - Olatinwo, Isa Adewale; Bakare, Akeem Adewale; Ogedengb, Frank Alaba; Gambo, Nasamu; Oyabambi, Adeniyi (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2025)
Effective communication remains one of the critical success factors in projects, especially since construction firms engage many stakeholders within a tight schedule. This paper investigates the influence of project communication structures and climate on the project quality of construction firms in North-Central Nigeria. This research adopts a quantitative research design through a physical administration of 5-point Likert-scale structure questionnaires to respondents in the industry. The statistical analysis was done using multiple regression with the aid of SPSS 27. Findings indicate that both dimensions of communication significantly determine project quality and overall project success. Results depict that clear communication structures enable the avoidance of misunderstandings and proper articulation of the project milestones. Also, an appropriate climate, one of communication indicative of trust, openness, and shared cooperation, reduces project delays. Consequently, the research recommends establishing clear, hierarchical communication channels to minimize ambiguities. This ensures critical information flows through designated pathways, reducing delays and misunderstandings. Also, the research recommends that construction forms foster a supportive communication environment by promoting transparency, trust, and active listening.